PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE DALAM MEMPREDIKSI FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Food & Beverage Yang Terdaftar di Bursa Efek Indonesia Tahun 2016 - 2018) - Yose Cahyo Benardi Widhayoga; Sri Sri (Sekolah Tinggi Ilmu Ekonomi Gici, 2021)
The development of food and beverage companies in Indonesia, will be a strong driver in competition. Fierce competition requires each company to think of a business strategy to gain market share and continue to maintain the company, so that bankruptcy will not occur. A company is established with the aim of obtaining profits through the main business carried out. The purpose of this study is to determine and analyze the Effect of Profitability, Liquidity and Leverage in Predicting Financial Distress. The type of research used is the associative research method. The data analysis model used is multiple linear analysis. The sample selection was carried out by purposive sampling and obtained samples of 14 companies from 20 listed companies. The results of the regression test showed that profitability, liquidity and leverage simultaneously affected the company's financial distress by 74.6%, as shown by the amount of adjusted R square of 74.6%, while the remaining 25.4% was influenced by other factors that were not included in the research model.